1981
DOI: 10.1002/chin.198149258
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: NEW METHOD FOR THE SYNTHESIS OF PHOSPHORYLATED FORMALS

Abstract: Phosphite wie (I) reagieren mit Diethoxymethylacetat (II) zu Phosphonaten wie (III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was reported that the reaction of trialkyl phosphites 58 with acetoxy(diethoxy)methane ( 61 ), which is more reactive derivative than orthoformate esters 54 [19,82], results in dialkyl (diethoxymethyl)phosphonates 62 (Scheme 10).…”
Section: Chemistry Of Phosphorylated Formaldehyde Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the reaction of trialkyl phosphites 58 with acetoxy(diethoxy)methane ( 61 ), which is more reactive derivative than orthoformate esters 54 [19,82], results in dialkyl (diethoxymethyl)phosphonates 62 (Scheme 10).…”
Section: Chemistry Of Phosphorylated Formaldehyde Derivativesmentioning
confidence: 99%
“…Alkyl alkyl(dialkoxymethyl)phosphinates 83 unsymmetrically substituted at the phosphorus atom were synthesized by the Arbuzov reaction of dialkyl (dialkoxymethyl)phosphonites 84 with alkyl iodides [82,84], for example see Scheme 16.…”
Section: Chemistry Of Phosphorylated Formaldehyde Derivativesmentioning
confidence: 99%